Optimizing the Molecular Weight of Poly(vinylidene Fluoride) for Competitive Perfluorosulfonic Acid Membranes. Issue 2 (13th December 2021) - Feng, Chao; Dong, Yunfa; Zhong, Shijie; Chen, Dongjiang; Zeng, Guangfeng; He, Weidong
Abstract : Homogeneous proton exchange membrane with high mechanical strength and low gas permeation is of paramount importance for the application of proton exchange membrane fuel cells (PEMFCs). Herein, the impact of different molecular weight of poly(vinylidene fluoride) (PVDF, M w  = 350 000–1 100 000 g mol −1 ) on the performance of the perfluorosulfonic acid (PFSA)/PVDF blend membrane is studied systematically for the first time. The mechanical strength of the PFSA/PVDF blend membrane increases and the H2 crossover of PFSA/PVDF blend membrane is decreased with increasing molecular weight of PVDF. Due to the fact that ultra‐high molecular weight PVDF has more long‐chain molecules which can enhance the adhesive strength between PVDF and PFSA, the tensile strength of 25 wt% PVDF5130–PFSA ( M w  = 1 100 000) membrane reaches 33.5 MPa with the thickness of 15 μm, 200% higher than that of pure PFSA membrane and 60% higher than that of commercial Nafion 211. The H2 crossover of the blend membrane is 0.69 mA cm −2, much lower than that of commercial Nafion 211 (2.05 mA cm −2 ). When applied in PEMFCs, the blend membrane shows comparable power density to Nafion 211 with an output of 1.17 W cm −2 . Abstract : Ultrahigh molecular weight Poly(vinylidene Fluoride) (PVDF) greatly improves the mechanical strength of perfluorosulfonic acid (PFSA) with 25% content blend due to reinforced adhesive strength between PVDF and PFSA. PVDF5130–PFSA blend membrane exhibits very high tensile strength up to 33.5 MPa and outstanding H2 /O2 fuel cell performance compared with commercial Nafion 211.